Full-scale collapse testing of a steel stiffened plate structure under axial-compressive loading triggered by brittle fracture at cryogenic condition. (30th December 2020) - Paik, Jeom Kee; Lee, Dong Hun; Noh, Sung Hwan; Park, Dae Kyeom; Ringsberg, Jonas W.
ABSTRACT: This paper is a sequel to the authors' earlier article Paik et al. [2020a. Full-scale collapse testing of a steel stiffened plate structure under cyclic axial-compressive loading, Structures, https://doi.org/10.1016/j.istruc.2020.05.026 ]. The aim of the paper was to present a test data on the ultimate compressive strength characteristics of a full-scale steel stiffened plate structure at cryogenic condition which may be due to unwanted release of liquefied gases. The test structure was fabricated in a shipyard using exactly the same welding technology as used in today's shipbuilding industry. It is observed that the test structure reaches the ultimate limit states triggered by brittle fracture, which is totally different from typical collapse modes at room temperature. Details of the test database are documented as they can be used to validate computational models for the structural crashworthiness analysis involving brittle fracture at cryogenic condition.